PENGARUH KEMUDAHAN, KEPERCAYAAN, DAN RISIKO TERHADAP MINAT PENGGUNAAN QRIS PADA KARYAWAN DI WILAYAH JAKARTA PUSAT TAHUN 2025 - Mutiara Armita; Ringkot P Nainggolan (Mount Hope Management International Journal, 2025)
The development of digital payment systems in Indonesia has experienced significant growth along with the implementation of the Quick Response Code Indonesia Standard (QRIS). The level of QRIS adoption by users is influenced by perceived ease of use, trust, and risk. This study aims to analyze the influence of ease of use, trust, and risk on the intention to use QRIS among employees in the Central Jakarta area in 2025. This study uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents selected using a purposive sampling technique. Data were analyzed using multiple linear regression with SPSS software through validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficients of determination (Adjusted R²). The results show that partially ease of use and trust have a positive and significant effect on the intention to use QRIS, with trust being the most dominant variable. Meanwhile, risk has no significant effect on intention to use. Simultaneously, ease of use, trust, and risk have a significant effect on intention to use QRIS. These findings indicate that increasing the perception of ease of use and strengthening the trust aspect are strategic factors in encouraging the adoption of QRIS-based digital payments.